The EFFECTIVENESS OF USING EDMODO IN ENHANCHING STUDENTS’ OUTCOMES IN ADVANCE REPORT OF CLASS ROOMACTION RESEARCH - Lailatul Masruroh (English Language Teaching Department (Prodi Pendidikan Bahasa Inggris), 2019)
ABSTRACT Media is one of the components that can influence the results of the learning process as well as allowing them to play. It is very much expected that they can enjoy the learning process in the classroom. In this issue, the media as a component of education really has a very important role. Recently some educators have tried to improve the quality of education by developing media and methods. Media also allows tutors to make variations in class because one of the medias can be applied in several methods. Media can be defined as a source for learning, so the ordinary media can influence learning effectiveness, in generally the media is divided into three parts, the first is audio (it can be heard),the second is visual (it can be seen) that third is audio visual (it can be seen and heard). And the purpose of this study is (1) to find out whether classroom action research using Edmodo media is better than the one that does not use (2) To describe how to applicate Edmodo media in the course of Classroom Action Research. The design of this study is quantitative research, and the design of this study uses experimental research. In this study, the data was taken from the 6th semester of students in STKIP Qomaruddin Gresik. There are 20 students in the class and the researcher will take all of these students and be taken as a population, because this research design uses pre-experimental so the researcher only needs one class as sample. After doing Pre-test students will be given treatment and training, after the material mastered in the specified schedule will be given, a post-test as a measure of Edmodo media, but from the post-test that students done, it was can be conclude that the Edmodo is not too good for students of 6th semester of STKIP Qomaruddin, because it is still 36.5 % students cannot make report of action research.